Sources and Effects of Oxidative Stress in Hypertension - Pinheiro, Lucas C.; Oliveira-Paula, Gustavo H. (Current Hypertension Reviews, 2020)
Background: Disruption of redox signaling is a common pathophysiological mechanism observed in several diseases. In hypertension, oxidative stress, resulted either from enhances in Reactive Oxygen Species (ROS) production or decreases in antioxidant defenses, is associated with increase in blood pressure, endothelial dysfunction and vascular remodeling. Although the role of oxidative stress in the development of hypertension is well known, it is still unclear if this process is a cause or a consequence of tissue changes in hypertension. Indeed, unbalanced ROS formation results in several detrimental effects that contribute to hypertension, including reduction in nitric oxide bioavailability and activation of metalloproteinases. Additionally, ROS may also directly react with lipids, proteins and DNA, thereby contributing to tissue damage associated with hypertension. Therefore, a deep understanding of the role of oxidative stress in hypertension is essential to comprehend its pathophysiology and to identify new therapeutic targets. Conclusion: This mini-review discusses the main enzymatic sources of oxidants and the major antioxidant defenses in the vasculature, followed by the effects of oxidative stress in hypertension, highlighting endothelial dysfunction, vascular remodeling and tissue damage.
Keywords: vascular remodeling